Aging exacerbates high‐fat diet‐induced steatohepatitis through alteration in hepatic lipid metabolism in mice. Issue 8 (17th February 2020) - Ishizuka, Kei; Kon, Kazuyoshi; Lee‐Okada, Hyeon‐Cheol; Arai, Kumiko; Uchiyama, Akira; Yamashina, Shunhei; Yokomizo, Takehiko; Ikejima, Kenichi
Abstract: Background and Aim: Aging is an independent risk factor for the progression of non‐alcoholic steatohepatitis. Here, we investigated the role of age‐related alterations in fatty acid metabolism in dietary steatohepatitis using lipidomics analysis. Methods: Male 8‐week and 55‐week‐old C57BL/6 J mice were fed a high‐fat diet (HFD) for 8 weeks. The quality and quantity of lipid molecular species in the liver were evaluated using the lipidomics approach. Results: Elder mice fed an HFD developed more severe steatohepatitis than young mice. Oxidative stress and inflammatory cytokines in the liver were exacerbated following HFD feeding in elder mice compared with young mice. In elder mice, de novo fatty acid synthesis was promoted, whereas β oxidation was blunted following HFD feeding, and lipid secretion from the liver was reduced. The expression of sirtuin 1 was not only reduced with age as expected but also significantly decreased due to intake of HFD. In the lipidomics analysis, the concentrations of diacylglycerol and TAG molecular species containing monounsaturated fatty acids were markedly increased following HFD feeding in elder mice compared with young mice. In contrast, the concentration of phosphatidylethanolamine and phosphatidylcholine molecular species containing polyunsaturated fatty acids were remarkably decreased following HFD feeding in elder mice compared with young mice, and the expression of fatty acid desaturase was blunted. Conclusions: Aging‐dependent alterations in lipid metabolism under excessive lipid supply most likely enhance hepatic lipotoxicity, thereby exacerbating metabolic steatohepatitis in elderly.